Humor in mathematics teaching can be a serious thing! - Menezes, Luís (2018)
This study focuses on the educational possibilities of instructional humour in the teaching of Mathematics in the final stages of primary education. It is an exploratory study whose main objective is to understand the role that mathematical tasks, based on humorous situations (cartoons or comic strips), might play in the learning of Mathematics and in the development of mathematical communication and mathematical knowledge. In order to reach this goal, three mathematical tasks, based on humorous cartoons involving mathematical concepts, were applied in a fourth-year class. Students worked in pairs in order to solve those given tasks. The work done by the students was then discussed collectively. The research adopted a qualitative methodology. The data collected come from class observation, audio recordings and from students’ written conclusions. The results reveal that those humour-based mathematical tasks have succeeded in catching students' attention to the learning of Mathematics. The students were able to understand the humorous situations depicted in the cartoons using their mathematical knowledge and were capable of developing that knowledge while solving the problems. The students wrote well developed texts based on the images presented, mobilizing their mathematical knowledge to understand the humour. The answers reveal students’ ability to combine their native language and mathematical language.